P4.040 Study to Explore the Sexual Behaviour and Practises, and Drug Use Pattern Among Female Injecting Drug Users in Sikkim. (13th July 2013) - Basu, R; Panda, N; RoyChowdhury, A; Sonkar, R Kr; Konar, S Das; Chowdhury, S; Kundu, M; Das, R
Abstract : Background: North East of India is a hub of Drug Use activities (NACO 2007). Although the government has specific programme to reduce the risks and vulnerabilities of Injecting Drug Users and cater to their health needs, it focuses on the male IDUs, ignoring the vulnerabilities of Female Injecting Drug Users; not recognising their separate needs. There is no Gender disaggregated data on IDUs available (UNODC 2004). Given that the socio-economic background and psychological conditions of FIDUs are different from their male counterparts (UNODC 2004), this study has been undertaken to study the sexual practises of and drug use pattern among FIDUs in Sikkim. Methods: The study has been conducted among FIDUs registered under the government projects operational in Sikkim. The sample had been selected on the basis of stratified random sampling. Structured Questionnaires had been developed and the Interviewers had been oriented on the research tool. Results: The study reveals that 73% of the FIDUs are sex workers, while 27% have multiple sexual partners. 36% inject drugs alone (70% have suffered overdose) while 64% inject drugs in groups. 80% of the respondents consume both injecting and non-injecting drugs. 39% are daily drug users and the rest weekly. 38% and 42% are using drugs since for last 6 months and over one year respectively, highlighting that drug use is an age old practise and there are continuous new entries. Although only 10% of the respondents use condoms, 89% use oral contraceptives thereby reducing chances of pregnancy but risk of STI and HIV remain. 57% of the respondents have suffered from STI. Conclusion: Thus, the study reveals that convergence of drugs related services and sexual & reproductive health services are essential. Unsafe injecting drug use combined with unprotected sex with multiple partners needs to be recognised and addressed through a comprehensive programme.